Sex differences in entrepreneurs' business growth intentions: An identity approach - Leonidas A. Zampetakis; Maria Bakatsaki; Konstantinos Kafetsios; Vassilis S. Moustakis (Journal of Innovation and Entrepreneurship, 2016)
The present empirical study explores the effects of gender role and cultural identity (masculinity and femininity) in mens' and womens' business growth intentions in established firms. A questionnaire survey was completed by 572 business owners (286 females). Results from moderated mediation regression analyses found that masculinity and femininity fully mediated the effects of entrepreneurs' sex on business growth intentions. Females who had higher femininity orientation and independent self-construal reported lower growth intention compared to those with lower independent self-construal. The study extends theoretical and empirical research on the effects of identity on business growth intentions while applications of the results are discussed.
Keywords: 650; Entrepreneurs; Growth intentions; Identity; Gender; Self-construal